Microbial community profiling of volcanic-affected rice soils near Mount Semeru, Lumajang, Indonesia using Next-Generation Sequencing for biofertilizer development - DWI NUR RIKHMA SARI; NI'MATUZAHROH NI'MATUZAHROH; FATIMAH FATIMAH; SALAMUN SALAMUN; MOCH AFFANDI; JUNAIRIAH JUNAIRIAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sari DNR, Ni’matuzahroh, Fatimah, Salamun, Affandi M, Junairiah. 2025. Microbial community profiling of volcanic-affected rice soils near Mount Semeru, Lumajang, Indonesia using Next-Generation Sequencing for biofertilizer development. Biodiversitas 26: 4424-4434. This study represents the first attempt to apply Next-Generation Sequencing (NGS) based on the 16S rRNA gene to analyze the microbial community structure in paddy soil affected by the eruption of Mount Semeru in Lumajang. This study aims to profile the microbial communities of volcanic-affected rice soils near Mount Semeru. Sequencing was conducted using ONT, with Guppy and NanoFilt for bioinformatic processing. Soil chemical analysis revealed a moisture content of 1.22%, organic carbon at 0.96%, and nitrogen at 0.1%. Available phosphorus was measured at 11 ppm, with a Cation Exchange Capacity (CEC) of 6.22 cmol(+)kg?¹. The microbial community was highly diverse, encompassing 100,046 observed species, with a Shannon-Wiener diversity index of 5.528 and estimated species richness values of 2,337.51 (Chao1) and 1,242.00 (ACE). This diversity spanned 44 phyla, 109 classes, and more than 5,000 species. The dominant phylum was Pseudomonadota (46.35% of total OTUs in the sample), with major genera including Lysobacter (5.90%) and Gaiella (4.44%). Opportunistic pathogens were also detected, underscoring the need to strengthen health and safety measures in post-eruption agricultural areas. These findings provide critical insights into the resilience of microbial communities and highlight their potential application in the development of biofertilizers and environmental biotechnology in Indonesia, offering hope for the future of agriculture in volcanic-affected areas.